1999
DOI: 10.1161/01.cir.99.6.817
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effect of Angiotensin-Converting Enzyme Inhibition Against Hypoxia/Reoxygenation Injury in Cultured Rat Cardiac Myocytes

Abstract: The present study demonstrates that cilazaprilat can directly protect myocytes against H/R injury, primarily as a result of an accumulation of bradykinin and the attendant production of NO induced by constitutive NO synthase in hypoxic myocytes in an autocrine/paracrine fashion. NO modulates guanylate cyclase and cGMP synthesis in myocytes, which may contribute to the preservation of energy metabolism and cardioprotection against H/R injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
1
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 29 publications
3
50
1
4
Order By: Relevance
“…Primary cultures of neonatal rat cardiac myocytes were prepared as described previously [21]. Cells were divided into 4 groups: a Control group in normal medium, a DOX group in medium with 1 μM DOX, a Cur group in medium with 5 μM Cur, and a DOX+Cur group in medium with 1 μM DOX and 5 μM Cur.…”
Section: Cardiomyocyte Isolations and Experimental Treatmentmentioning
confidence: 99%
“…Primary cultures of neonatal rat cardiac myocytes were prepared as described previously [21]. Cells were divided into 4 groups: a Control group in normal medium, a DOX group in medium with 1 μM DOX, a Cur group in medium with 5 μM Cur, and a DOX+Cur group in medium with 1 μM DOX and 5 μM Cur.…”
Section: Cardiomyocyte Isolations and Experimental Treatmentmentioning
confidence: 99%
“…Importantly, we did not observe any effect of ACE-AS on ACE mRNA, yet there was a marked decrease in the ACE protein expression, which indicates that the mechanism by which ACE-AS reduces ACE protein involves the post-transcriptional process. 20 A number of experimental and clinical studies show that ACE inhibitors are beneficial in treating acute myocardial infarction, and the benefits include preservation of left ventricular function 12,16 and myocardial cell integGene Therapy rity, 13,36 and reduction in reperfusion arrhythmias 15,16,37 and remodeling of myocardium. 36,38 However, chemical ACE inhibitors have several disadvantages, which include unpleasant side-effects 39 and need for frequent intake.…”
Section: Discussionmentioning
confidence: 99%
“…Others and ourselves have used this model extensively to study regulation of a variety of receptors and modulation of cardiac function by different agents. 13,25,26 In the isolated beating heart, cardiac function can be assessed independently of the influence of circulating blood cells and hormones, which may be considered an important advantage of this model. MDA, a lipid peroxidation product, and LDH, an enzyme in the cellular plasma, have also been previously used as indexes of tissue injury after ischemia/reperfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly in several studies, hypoxia is the direct trigger and well-known stimulus of apoptosis independent of the neuronhumoral factors in various physiologic and pathologic conditions. 8) Some studies have indicated that ANP and CNP inhibit vascular smooth muscle growth [9][10][11] and ANP induces apoptosis in cultured vascular smooth muscle cells, 12) which infer the negative effect of natriuretic peptides on the cardiovascular system. In this regard, the role of BNP in mild hypoxia-induced cardiomyocytes apoptosis and the possible mechanism are of great interest to explore.…”
mentioning
confidence: 99%